Rare earth reinforced high-strength and high-conductivity CuNiSiCoMg copper alloy and preparation method thereof
By adding rare earth elements to Cu-Ni-Si-Co-Mg alloy and adopting multi-stage rolling and aging technology, the contradiction between conductivity and strength of copper alloys is solved, and the performance of high-strength and high-conductivity of copper alloys is achieved, meeting the high-performance needs of integrated circuit lead frame materials.
Patent Information
- Application Number
- CN202411990744.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
While ensuring the conductivity of existing copper alloys, it is difficult to significantly improve their strength, and there is a contradiction between strength and conductivity.
By adding different contents of rare earth elements, such as Ce or La, to the Cu-Ni-Si-Co-Mg alloy, and using multi-stage rolling and aging process, the microstructure and precipitation phase are optimized to improve the mechanical properties and conductive properties of the copper alloy.
The high-strength and high conductivity of rare earth-enhanced CuNiSiCoMg copper alloy is achieved, and can meet the high-performance needs of integrated circuit lead frame materials.
Smart Images

Figure CN119776697A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloys, and in particular to a rare earth reinforced high-strength and high-conductivity CuNiSiCoMg copper alloy and a preparation method thereof. Background Art
[0002] Integrated circuit lead frame materials are key materials that are the foundation of chip manufacturing. Copper alloy strips are the most widely used structural conductive and heat dissipating materials in chip assembly. With the rapid development of computer and 5G communication technology, the integration and functionality of chips have been rapidly improved, which has put forward higher requirements on the strength, conductivity, thermal conductivity, elasticity and dimensional stability of lead frame materials. Therefore, Cu-Ni-Si alloy strips with high strength, medium conductivity and heat resistance have received widespread attention.
[0003] Cu-Ni-Si series alloys have high strength, moderate electrical and thermal conductivity, good resistance to high temperature softening and other comprehensive properties. Therefore, they have received more and more attention and are regarded as the representative of high-end lead frame copper alloy materials. It is particularly important to develop Cu-Ni-Si series alloy strips and their new production processes to achieve large-scale production and application of key materials for high-end lead frames. However, for copper alloys, high strength and high conductivity are contradictory. While ensuring that the conductivity is within a certain range, significantly improving the strength of copper alloys is the key to the research of high-strength and high-conductivity copper alloys. Summary of the invention
[0004] The purpose of the present invention is to provide a rare earth reinforced high-strength and high-conductivity CuNiSiCoMg copper alloy and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art and meet the high performance requirements of integrated circuit lead frame materials.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] The present invention provides a rare earth reinforced CuNiSiCoMg copper alloy, the mass contents of the components are as follows:
[0007] Ni 1.7-1.9%, Si 0.55-0.65%, Co 1.0-1.2%, Mg0.1-0.15%, rare earth elements 0-0.2%, and rare earth elements are not 0%, and the balance is Cu;
[0008] The rare earth element is Ce or La.
[0009] The present invention also provides a method for preparing the rare earth reinforced CuNiSiCoMg copper alloy, comprising the following steps:
[0010] (1) melting the alloy raw materials and casting them into ingots according to the mass content ratio of the components;
[0011] (2) subjecting the ingot material obtained in step (1) to a solid solution treatment, and then sequentially performing hot rolling and rough rolling and then a first aging treatment;
[0012] (3) The alloy material treated in step (2) is subjected to a first fine rolling and then a second aging treatment, air-cooled to room temperature, and then subjected to a third aging treatment after the second fine rolling, and air-cooled to room temperature to obtain the rare earth reinforced CuNiSiCoMg copper alloy.
[0013] Furthermore, the temperature of the solution treatment is 830-870°C and the time is 5 hours.
[0014] Furthermore, in step (2), the hot rolling temperature is 760-800°C, and the hot rolling reduction is 50-55%; more preferably, the hot rolling reduction is 30%.
[0015] Furthermore, in step (2), the temperature of the rough rolling is room temperature, and the reduction amount of the rough rolling is 80-85%; more preferably, the reduction amount of a single pass is 80-85%.
[0016] Furthermore, the temperature of the first aging treatment is 430° C. and the time is 4 hours; the temperature of the second aging treatment is 320° C. and the time is 4 hours; the temperature of the third aging treatment is 280-450° C. and the time is 0.5-4 hours.
[0017] Furthermore, the temperature of the first finishing rolling is room temperature, and the reduction is 70-80%; more preferably, the reduction in a single pass is 10%.
[0018] Furthermore, the temperature of the second finishing rolling is room temperature, and the reduction is 50-55%; more preferably, the reduction in a single pass is 5%.
[0019] The more specific method of the present invention for preparing rare earth reinforced high-strength and high-conductivity CuNiSiCoMg copper alloy comprises the following steps:
[0020] (1) preparing raw materials according to the alloy composition mass fraction of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.12%, rare earth elements: 0-0.2%, and the balance: Cu;
[0021] (2) Add the prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles into the graphite crucible in the vacuum induction melting furnace, seal the high-purity magnesium particles and Cu-Ce master alloy (or Cu-La master alloy) into the secondary feeding copper tube, close the melting furnace and evacuate, then introduce argon gas to a pressure of 0.04-0.05Mpa. The metal particles in the crucible are completely melted by induction heating, and then allowed to stand for 2-3 minutes. The high-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and then allowed to stand for 3-5 minutes. Finally, the alloy melt is poured into the mold, and the ingot is taken out after cooling to room temperature;
[0022] (3) The alloy ingot was cut into blocks by wire cutting, and then solution treated. After being kept at 850℃ for 5h, it was water cooled to room temperature. After being polished with sandpaper, surface impurities were cleaned with acetone and alcohol. After the alloy sample was kept at 780℃ for 0.5h, it was immediately hot rolled on a two-roll mill. The rolling conditions were: single pass 30%, roll speed 30 rpm, and hot rolling reduction of 50-55%. After the alloy sample was air cooled to room temperature, it was rough rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 80-85%. The rough-rolled sample was aged. The aging conditions were: annealing at 430℃ for 4h.
[0023] (4) After aging, the sample was polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The first finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 10%, roll speed 20 rpm, and rolling reduction of 70-80%. After rolling, annealing was carried out at 320℃ for 4h, air-cooled to room temperature, polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The second finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 5%, roll speed 20 rpm, and rolling reduction of 50-55%. After finishing rolling, the final aging treatment was carried out at 280-450℃ for 0.5-4h, and air-cooled to room temperature after aging. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.
[0024] The invention also provides a rare earth reinforced CuNiSiCoMg copper alloy prepared by the preparation method.
[0025] The present invention further provides application of the rare earth reinforced CuNiSiCoMg copper alloy as an integrated circuit lead frame material.
[0026] In the present invention, the Co element can promote the precipitation of (Ni, Co)2Si phase in the copper alloy and reduce the solute atom content in the matrix; the Mg element can promote the complete precipitation of the precipitated phase in the copper alloy; the rare earth Ce element can purify the copper matrix and grain boundaries, refine the microstructure, and have a certain improvement effect on the electrical conductivity and mechanical properties.
[0027] The invention strengthens the CuNiSiCoMg copper alloy by rare earth and obtains the copper alloy with good mechanical property and electrical conductivity by optimizing the rolling and aging process.
[0028] The present invention adds different contents of rare earth elements to the Cu-Ni-Si-Co-Mg alloy, combines with harmful impurity elements in the copper liquid during alloy smelting, purifies the liquid phase components, and the rare earth compounds formed can inhibit grain growth, thereby refining the copper alloy microstructure and promoting the precipitation of second phase particles; through multi-stage rolling: hot rolling + rough rolling + finishing rolling, combined with multiple aging treatment processes, the copper alloy is fully precipitated with fine and uniform second phase (Ni, Co) 2Si, exerting the precipitation strengthening effect. By regulating the microstructure and precipitation phase in the copper alloy, the electrical conductivity and mechanical properties of the copper alloy are optimized.
[0029] The present invention discloses the following technical effects:
[0030] In order to further improve the mechanical properties and electrical conductivity of Cu-Ni-Si alloy strips for high-end integrated circuit lead frames, the present invention provides a rare earth reinforced high-strength and high-conductivity Cu-Ni-Si-Co-Mg alloy and a preparation method thereof, which promotes the full precipitation of precipitated phases in the copper alloy through multiple rolling and aging processes, and purifies the grain boundaries and refines the grains through the addition of rare earth, thereby finally obtaining a copper alloy with good electrical conductivity and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 The present invention is a flow chart for preparing the rare earth reinforced high-strength and high-conductivity CuNiSiCoMg copper alloy.
[0033] Figure 2 This is a microscopic morphology of the rare earth Ce reinforced high-strength and high-conductivity CuNiSiCoMg copper alloy prepared in Example 1 of the present invention.
[0034] Figure 3 The electrical conductivity of copper alloys with different Ce contents prepared in Examples 1-2 of the present invention and Comparative Example 1 (respectively marked as 0.1% Ce, 0.2% Ce and 0% Ce) after the third aging treatment at different treatment temperatures for different times, wherein a is 280°C, b is 300°C, c is 320°C, and d is 350°C.
[0035] Figure 4 The tensile strength of copper alloys with different Ce contents prepared in Examples 1-2 of the present invention and Comparative Example 1 (marked as 0.1% Ce, 0.2% Ce and 0% Ce, respectively) after the third aging treatment at different treatment temperatures for different times, wherein a is 280°C, b is 300°C, c is 320°C, and d is 350°C.
[0036] Figure 5 The electrical conductivity of copper alloys with different La contents prepared in Examples 4-5 of the present invention and Comparative Example 2 (respectively marked as 0.1% La, 0.2% La and 0% La) after the third aging treatment at different treatment temperatures for different times, wherein a is 280°C, b is 300°C, c is 320°C, and d is 350°C.
[0037] Figure 6 The tensile strength of copper alloys with different La contents prepared in Examples 4-5 of the present invention and Comparative Example 2 (respectively marked as 0.1% La, 0.2% La and 0% La) after the third aging treatment at different treatment temperatures for different times, wherein a is 280°C, b is 300°C, c is 320°C, and d is 350°C. DETAILED DESCRIPTION
[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0039] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0043] Figure 1 The present invention is a flow chart for preparing the rare earth reinforced high-strength and high-conductivity CuNiSiCoMg copper alloy.
[0044] Example 1
[0045] A method for preparing a rare earth Ce-reinforced high-strength and high-conductivity CuNiSiCoMg copper alloy, the steps are as follows:
[0046] (1) Prepare raw materials according to the alloy composition mass fraction of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.12%, Ce: 0.1%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, the purity of Co is ≥99.99%, the purity of Mg is ≥99.99%, and the Cu-Ce master alloy (wt.%Cu+Ce≥99.99%, wt.%Ce=10%).
[0047] (2) Add the prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles into the graphite crucible in the vacuum induction melting furnace, seal the high-purity magnesium particles and Cu-Ce master alloy into the secondary feeding copper tube, close the melting furnace and evacuate the air to 13Pa, then introduce argon gas to a pressure of 0.05Mpa. The metal particles in the crucible are completely melted by induction heating, and then allowed to stand for 3 minutes. The high-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and then allowed to stand for 5 minutes. Finally, the alloy melt is poured into the mold, and the ingot is taken out after cooling to room temperature.
[0048] (3) The alloy ingot was cut into blocks by wire cutting, and then solution treated. After being kept at 850℃ for 5h, it was water cooled to room temperature. After being polished with sandpaper, surface impurities were cleaned with acetone and alcohol. After the alloy sample was kept at 780℃ for 0.5h, it was immediately hot rolled on a two-roll mill. The rolling conditions were: single pass 30%, roll speed 30 rpm, and hot rolling reduction of 50%. After the alloy sample was air cooled to room temperature, it was rough rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 85%. The rough-rolled sample was aged. The aging conditions were: annealing at 430℃ for 4h.
[0049] (4) After aging, the sample was polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The first finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 10%, roll speed 20 rpm, and rolling reduction of 80%. After rolling, it was annealed at 320℃ for 4h, air-cooled to room temperature, polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The second finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 5%, roll speed 20 rpm, and rolling reduction of 50%. After finishing rolling, the final aging treatment was carried out at 300℃ for 0.5h, and air-cooled to room temperature after aging. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.
[0050] Example 2
[0051] A method for preparing a rare earth Ce-reinforced high-strength and high-conductivity CuNiSiCoMg copper alloy, the steps are as follows:
[0052] (1) Prepare raw materials according to the alloy composition mass fraction of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.12%, Ce: 0.2%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, the purity of Co is ≥99.99%, the purity of Mg is ≥99.99%, and the Cu-Ce master alloy (wt.%Cu+Ce≥99.99%, wt.%Ce=10%).
[0053] (2) Add the prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles into the graphite crucible in the vacuum induction melting furnace, seal the high-purity magnesium particles and Cu-Ce master alloy into the secondary feeding copper tube, close the melting furnace and evacuate the air to 13Pa, then introduce argon gas to a pressure of 0.05Mpa. The metal particles in the crucible are completely melted by induction heating, and then allowed to stand for 3 minutes. The high-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and then allowed to stand for another 3 minutes. Finally, the alloy melt is poured into a mold, and the ingot is taken out after cooling to room temperature.
[0054] (3) The alloy ingot was cut into blocks by wire cutting, and then solution treated. After being kept at 850℃ for 5h, it was water cooled to room temperature. After being polished with sandpaper, surface impurities were cleaned with acetone and alcohol. After the alloy sample was kept at 780℃ for 0.5h, it was immediately hot rolled on a two-roll mill. The rolling conditions were: single pass 30%, roll speed 30 rpm, and hot rolling reduction of 50%. After the alloy sample was air cooled to room temperature, it was rough rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 80%. The rough-rolled sample was aged. The aging conditions were: annealing at 430℃ for 4h.
[0055] (4) After aging, the sample was polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The first finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 10%, roll speed 20 rpm, and rolling reduction of 75%. After rolling, annealing was carried out at 320℃ for 4h, air-cooled to room temperature, polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The second finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 5%, roll speed 20 rpm, and rolling reduction of 50%. After finishing rolling, the final aging treatment was carried out at 280℃ for 1h, and air-cooled to room temperature after aging. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.
[0056] Example 3
[0057] A method for preparing a rare earth Ce-reinforced high-strength and high-conductivity CuNiSiCoMg copper alloy, the steps are as follows:
[0058] (1) Prepare raw materials according to the alloy composition mass fraction of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.12%, Ce: 0.1%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, the purity of Co is ≥99.99%, the purity of Mg is ≥99.99%, and the Cu-Ce master alloy (wt.% Cu+Ce≥99.99%, wt.%
[0059] Ce=10%).
[0060] (2) Add the prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles into the graphite crucible in the vacuum induction melting furnace, seal the high-purity magnesium particles and Cu-Ce master alloy into the secondary feeding copper tube, close the melting furnace and evacuate the air to 13Pa, then introduce argon gas to a pressure of 0.05Mpa. The metal particles in the crucible are completely melted by induction heating, and then allowed to stand for 3 minutes. The high-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and then allowed to stand for 5 minutes. Finally, the alloy melt is poured into the mold, and the ingot is taken out after cooling to room temperature.
[0061] (3) The alloy ingot was cut into blocks by wire cutting, and then solution treated. After being kept at 850℃ for 5h, it was water cooled to room temperature. After being polished with sandpaper, surface impurities were cleaned with acetone and alcohol. After the alloy sample was kept at 780℃ for 0.5h, it was immediately hot rolled on a two-roll mill. The rolling conditions were: single pass 30%, roll speed 30 rpm, and hot rolling reduction of 50%. After the alloy sample was air cooled to room temperature, it was rough rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 85%. The rough-rolled sample was aged. The aging conditions were: annealing at 430℃ for 4h.
[0062] (4) After aging, the sample was polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The first finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 10%, roll speed 20 rpm, and rolling reduction of 70%. After rolling, it was annealed at 320℃ for 4h, air-cooled to room temperature, polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The second finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 5%, roll speed 20 rpm, and rolling reduction of 50%. After finishing rolling, the final aging treatment was carried out at 350℃ for 2h, and air-cooled to room temperature after aging. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.
[0063] Comparative Example 1
[0064] A method for preparing a CuNiSiCoMg copper alloy, comprising the following steps:
[0065] (1) Prepare raw materials according to the alloy composition mass fraction of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.12%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, the purity of Co is ≥99.99%, and the purity of Mg is ≥99.99%.
[0066] (2) Add the prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles into the graphite crucible in the vacuum induction melting furnace, seal the high-purity magnesium particles into the secondary feeding copper tube, close the melting furnace and evacuate the air to 13Pa, then introduce argon gas to a pressure of 0.04Mpa. The metal particles in the crucible are completely melted by induction heating, and then allowed to stand for 3 minutes. The high-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and then allowed to stand for another 3 minutes. Finally, the alloy melt is poured into a mold, and the ingot is taken out after cooling to room temperature.
[0067] (3) The alloy ingot was cut into blocks by wire cutting, and then solution treated. After being kept at 850℃ for 5h, it was water cooled to room temperature. After being polished with sandpaper, surface impurities were cleaned with acetone and alcohol. After the alloy sample was kept at 780℃ for 0.5h, it was immediately hot rolled on a two-roll mill. The rolling conditions were: single pass 30%, roll speed 30 rpm, and hot rolling reduction of 55%. After the alloy sample was air cooled to room temperature, it was rough rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 80%. The rough-rolled sample was aged. The aging conditions were: annealing at 430℃ for 4h.
[0068] (4) After aging, the sample was polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The first finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 10%, roll speed 20 rpm, and rolling reduction of 80%. After rolling, it was annealed at 320℃ for 4h, air-cooled to room temperature, polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The second finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 5%, roll speed 20 rpm, and rolling reduction of 55%. After finishing rolling, the final aging treatment was carried out at 320℃ for 2h, and air-cooled to room temperature after aging. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.
[0069] Figure 2 This is a microscopic morphology of the rare earth Ce reinforced high-strength and high-conductivity CuNiSiCoMg copper alloy prepared in Example 1.
[0070] The present invention further investigates the electrical conductivity of copper alloys with different Ce contents prepared in Examples 1-2 and Comparative Example 1 (respectively marked as 0.1% Ce, 0.2% Ce and 0% Ce) after the third aging treatment at different treatment temperatures for different times. The results are as follows: Figure 3 As shown in the figure, a is 280°C, b is 300°C, c is 320°C, and d is 350°C.
[0071] The present invention also investigates the tensile strength of copper alloys with different Ce contents prepared in Examples 1-2 and Comparative Example 1 (respectively marked as 0.1% Ce, 0.2% Ce and 0% Ce) after the third aging treatment at different treatment temperatures for different times. The results are as follows: Figure 4 As shown in the figure, a is 280°C, b is 300°C, c is 320°C, and d is 350°C.
[0072] Example 4
[0073] A method for preparing a rare earth La-reinforced high-strength and high-conductivity CuNiSiCoMg copper alloy, comprising the following steps:
[0074] (1) Prepare raw materials according to the alloy composition mass fraction of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.12%, La: 0.1%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, the purity of Co is ≥99.99%, the purity of Mg is ≥99.99%, and the Cu-La master alloy (wt.%Cu+La≥99.99%, wt.%La=10%) is prepared.
[0075] (2) Add the prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles into the graphite crucible in the vacuum induction melting furnace, seal the high-purity magnesium particles and Cu-La master alloy into the secondary feeding copper tube, close the melting furnace and evacuate the air to 13Pa, then introduce argon gas to a pressure of 0.04Mpa. The metal particles in the crucible are completely melted by induction heating, and then allowed to stand for 3 minutes. The high-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and then allowed to stand for another 3 minutes. Finally, the alloy melt is poured into a mold, and the ingot is taken out after cooling to room temperature.
[0076] (3) The alloy ingot was cut into blocks by wire cutting, and then solution treated. After being kept at 850℃ for 5h, it was water cooled to room temperature. After being polished with sandpaper, surface impurities were cleaned with acetone and alcohol. After the alloy sample was kept at 780℃ for 0.5h, it was immediately hot rolled on a two-roll mill. The rolling conditions were: single pass 30%, roll speed 30 rpm, and hot rolling reduction of 55%. After the alloy sample was air cooled to room temperature, it was rough rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 85%. The rough-rolled sample was aged. The aging conditions were: annealing at 430℃ for 4h.
[0077] (4) After aging, the sample was polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The first finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 10%, roll speed 20 rpm, and rolling reduction of 80%. After rolling, it was annealed at 320℃ for 4h, air-cooled to room temperature, polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The second finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 5%, roll speed 20 rpm, and rolling reduction of 50%. After finishing rolling, the final aging treatment was carried out at 300℃ for 0.5h, and air-cooled to room temperature after aging. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.
[0078] Example 5
[0079] A method for preparing a rare earth La-reinforced high-strength and high-conductivity CuNiSiCoMg copper alloy, comprising the following steps:
[0080] (1) Prepare raw materials according to the alloy composition mass fraction of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.12%, La: 0.2%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, the purity of Co is ≥99.99%, the purity of Mg is ≥99.99%, and the Cu-La master alloy (wt.%Cu+La≥99.99%, wt.%La=10%) is prepared.
[0081] (2) Add the prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles into the graphite crucible in the vacuum induction melting furnace, seal the high-purity magnesium particles and Cu-La master alloy into the secondary feeding copper tube, close the melting furnace and evacuate the air to 13Pa, then introduce argon gas to a pressure of 0.04Mpa. The metal particles in the crucible are completely melted by induction heating, and then allowed to stand for 5 minutes. The high-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and then allowed to stand for 3 minutes. Finally, the alloy melt is poured into a mold, and the ingot is taken out after cooling to room temperature.
[0082] (3) The alloy ingot was cut into blocks by wire cutting, and then solution treated. After being kept at 850℃ for 5h, it was water cooled to room temperature. After being polished with sandpaper, surface impurities were cleaned with acetone and alcohol. After the alloy sample was kept at 780℃ for 0.5h, it was immediately hot rolled on a two-roll mill. The rolling conditions were: single pass 30%, roll speed 30 rpm, and hot rolling reduction of 50%. After the alloy sample was air cooled to room temperature, it was rough rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 85%. The rough-rolled sample was aged. The aging conditions were: annealing at 430℃ for 4h.
[0083] (4) After aging, the sample was polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The first finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 10%, roll speed 20 rpm, and rolling reduction of 75%. After rolling, annealing was carried out at 320℃ for 4h, air-cooled to room temperature, polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The second finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 5%, roll speed 20 rpm, and rolling reduction of 50%. After finishing rolling, the final aging treatment was carried out at 280℃ for 1h, and air-cooled to room temperature after aging. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.
[0084] Example 6
[0085] A method for preparing a rare earth La-reinforced high-strength and high-conductivity CuNiSiCoMg copper alloy, comprising the following steps:
[0086] (1) Prepare raw materials according to the alloy composition mass fraction of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.12%, La: 0.1%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, the purity of Co is ≥99.99%, the purity of Mg is ≥99.99%, and the Cu-Ce master alloy (wt.%Cu+La≥99.99%, wt.%La=10%).
[0087] (2) Add the prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles into the graphite crucible in the vacuum induction melting furnace, seal the high-purity magnesium particles and Cu-La master alloy into the secondary feeding copper tube, close the melting furnace and evacuate the air to 13Pa, then introduce argon gas to a pressure of 0.05Mpa. The metal particles in the crucible are completely melted by induction heating, and then allowed to stand for 3 minutes. The high-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and then allowed to stand for 5 minutes. Finally, the alloy melt is poured into a mold, and the ingot is taken out after cooling to room temperature.
[0088] (3) The alloy ingot was cut into blocks by wire cutting, and then solution treated. After being kept at 850℃ for 5h, it was water cooled to room temperature. After being polished with sandpaper, surface impurities were cleaned with acetone and alcohol. After the alloy sample was kept at 780℃ for 0.5h, it was immediately hot rolled on a two-roll mill. The rolling conditions were: single pass 30%, roll speed 30 rpm, and hot rolling reduction of 50%. After the alloy sample was air cooled to room temperature, it was rough rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 85%. The rough-rolled sample was aged. The aging conditions were: annealing at 430℃ for 4h.
[0089] (4) After aging, the sample was polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The first finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 10%, roll speed 20 rpm, and rolling reduction of 70%. After rolling, it was annealed at 320℃ for 4h, air-cooled to room temperature, polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The second finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 5%, roll speed 20 rpm, and rolling reduction of 50%. After finishing rolling, the final aging treatment was carried out at 350℃ for 2h, and air-cooled to room temperature after aging. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.
[0090] Comparative Example 2
[0091] A method for preparing a CuNiSiCoMg copper alloy, comprising the following steps:
[0092] (1) Prepare raw materials according to the alloy composition mass fraction of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.12%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, the purity of Co is ≥99.99%, and the purity of Mg is ≥99.99%.
[0093] (2) Add the prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles into the graphite crucible in the vacuum induction melting furnace, seal the high-purity magnesium particles into the secondary feeding copper tube, close the melting furnace and evacuate the air to 13Pa, then introduce argon gas to a pressure of 0.05Mpa. The metal particles in the crucible are completely melted by induction heating, and then allowed to stand for 3 minutes. The high-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and then allowed to stand for another 3 minutes. Finally, the alloy melt is poured into a mold, and the ingot is taken out after cooling to room temperature.
[0094] (3) The alloy ingot was cut into blocks by wire cutting, and then solution treated. After being kept at 860℃ for 5h, it was water cooled to room temperature. After being polished with sandpaper, surface impurities were cleaned with acetone and alcohol. After the alloy sample was kept at 780℃ for 0.5h, it was immediately hot rolled on a two-roll mill. The rolling conditions were: single pass 30%, roll speed 30 rpm, and hot rolling reduction of 50%. After the alloy sample was air cooled to room temperature, it was rough rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 82%. The rough-rolled sample was aged. The aging conditions were: annealing at 430℃ for 4h.
[0095] (4) After aging, the sample was polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The first finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 10%, roll speed 20 rpm, and rolling reduction of 80%. After rolling, it was annealed at 320℃ for 4h, air-cooled to room temperature, polished with sandpaper, and the surface impurities were cleaned with acetone and alcohol. The second finishing rolling was carried out on a four-roll mill. The rolling conditions were: room temperature, single pass 5%, roll speed 20 rpm, and rolling reduction of 55%. After finishing rolling, the final aging treatment was carried out at 320℃ for 2h, and air-cooled to room temperature after aging. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.
[0096] The present invention further investigates the electrical conductivity of copper alloys with different La contents prepared in Examples 4-5 and Comparative Example 2 (respectively marked as 0.1% La, 0.2% La and 0% La) after the third aging treatment at different treatment temperatures for different times. The results are as follows: Figure 5 As shown in the figure, a is 280°C, b is 300°C, c is 320°C, and d is 350°C.
[0097] The present invention also investigates the tensile strength of copper alloys with different La contents prepared in Examples 4-5 and Comparative Example 2 (respectively marked as 0.1% La, 0.2% La and 0% La) after the third aging treatment at different treatment temperatures for different times. The results are as follows: Figure 6 As shown in the figure, a is 280°C, b is 300°C, c is 320°C, and d is 350°C.
[0098] The rare earth reinforced CuNiSiCoMg copper alloy prepared by the present invention has excellent performance and can meet the use requirements of integrated circuit lead frame materials.
[0099] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A rare earth enhanced CuNiSiCoMg copper alloy, characterized in that: The mass contents of the components are as follows: Ni 1.7-1.9%, Si 0.55-0.65%, Co 1.0-1.2%, Mg 0.1-0.15%, rare earth element 0-0.2%, and the rare earth element is not 0%, and the balance is Cu; the rare earth element is Ce or La.
2. The method for preparing the rare earth enhanced CuNiSiCoMg copper alloy according to claim 1, characterized in that: The following steps are involved: (1) melting the alloy raw materials and casting them into ingots according to the mass content ratio of the components; (2) subjecting the ingot material obtained in step (1) to a solid solution treatment, and then sequentially performing hot rolling and rough rolling and then a first aging treatment; (3) The alloy material treated in step (2) is subjected to a first fine rolling and then a second aging treatment, air-cooled to room temperature, and then subjected to a third aging treatment after the second fine rolling, and air-cooled to room temperature to obtain the rare earth reinforced CuNiSiCoMg copper alloy.
3. The preparation method according to claim 2, characterized in that: The temperature of the solution treatment is 830-870° C. and the time is 5 hours.
4. The preparation method according to claim 2, characterized in that: In step (2), the hot rolling temperature is 760-800° C., and the hot rolling reduction is 50-55%.
5. The preparation method according to claim 2, characterized in that: The temperature of the rough rolling in step (2) is room temperature, and the reduction amount of the rough rolling is 80-85%.
6. The preparation method according to claim 2, characterized in that: The temperature of the first aging treatment is 430° C. and the time is 4 hours; the temperature of the second aging treatment is 320° C. and the time is 4 hours; the temperature of the third aging treatment is 280-450° C. and the time is 0.5-4 hours.
7. The preparation method according to claim 2, characterized in that: The temperature of the first finishing rolling is room temperature, and the reduction is 70-80%.
8. The preparation method according to claim 2, characterized in that: The temperature of the second finishing rolling is room temperature, and the reduction is 50-55%.
9. The rare earth reinforced CuNiSiCoMg copper alloy prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the rare earth reinforced CuNiSiCoMg copper alloy as claimed in claim 9 as an integrated circuit lead frame material.
Citation Information
Patent Citations
High-strength Cu-Ni-Co-Si base copper alloy sheet, process for producing same, and current-carrying component
CN104968815A
High-strength and high-elasticity copper-nickel-silicon-cobalt-system lead frame machining technology
CN107988512A
Method for simultaneously improving mechanical property and conductivity of Cu-Ni-Si-Co copper alloy
CN117305740A
Copper-nickel-silicon alloy strip for high-strength and high-conductivity lead frame and preparation method of copper-nickel-silicon alloy strip
CN118326203A
Method for manufacturing copper alloy sheet material
JP2015187308A